Evaluation of full scale shear performance of tension anchor foundations: Load displacement curves and failure criteria. (1st February 2017) - Bergamo, Paolo; Donohue, Shane; Callan, Damian; Holland, Adam; McCarey, John; Brown, William; McSherry, Michael; Ward, Cillian; Amato, Giuseppina; Sivakumar, V.
Abstract: One of the biggest challenges faced by the offshore wave and tidal energy industry is the high cost of constructing and installing offshore foundations. Foundations based on post tensioned pile anchors can be effectively proposed to tackle this issue. A series of full-scale direct shear tests were performed on-shore to evaluate the shear resistance of post-tensioned pile anchor foundations designed for securing tidal turbine devices to a rock seabed. We focused, in particular, on the primary shear resistance mechanism of post-tensioned anchors, by applying a vertical force which mobilizes, a frictional force able to resist horizontal thrusts. Different load paths, involving monotonic or cyclic loading, were applied; several configurations for the footing of the foundation were tested. The footing stress-displacement behavior and the stress conditions at sliding failure from a number of different testing configurations were compared and analyzed. A marked consistency with the shear performance of natural rock joints was identified. This allows the behavior of tension pile foundations subjected to substantial horizontal loads to be modeled using relationships developed for rock joints, widely available in the literature. Additionally, the results obtained from different tests were also collated considering the various configurations adopted for the foundation-rock system and the applied load paths, to identify the factors that affect the shear resistance of the foundation. Highlights: Full-scale direct shear tests were performed to evaluate the shear resistance of tension anchor foundations. Different load paths were applied (monotonic and cyclic) using several footing configurations. Stress-displacement behavior and the stress conditions at sliding failure were compared and analyzed. The footing behavior was consistent with the expected shear performance of natural rock joints. A range of factors that affect the shear resistance of the foundation were identified.